THE CHILEAN RIGHT WING AND SOCIAL POLICY, 1990-2019 - Miranda Rozas, Carlos Javier (Revista de Historia Social y de las Mentalidades, 2022)
This paper will attempt to demonstrate that the supposed negative disposition of the right concerning social policy, derived from its adherence to neoliberalism, is a prejudice that does not represent the actual positions adopted by this political sector in recent decades. The various sources analysed to show that the right does not have an unrestricted adherence to the theoretical postulates of neoliberalism nor to the formulas it promoted in practice. Finally, we argue that for the right wing, the central problem, in terms of social policy, is related to the interests of the property-owning sectors
Keywords: Chilean Right-wing; Social Policy; Neoliberalism; Subsidiarity; Businessman; Recent Political History